2006
DOI: 10.1002/ajmg.a.31435
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotype and molecular characterization of 6q terminal deletion syndrome: Five new cases

Abstract: Mental retardation, facial dysmorphisms, seizures, and brain abnormalities are features of 6q terminal deletions. We have ascertained five patients with 6q subtelomere deletions (four de novo, one as a result of an unbalanced translocation) and determined the size of the deletion ranging from 3 to 13 Mb. Our patients showed a recognizable phenotype including mental retardation, characteristic facial appearance, and a distinctive clinico-neuroradiological picture. Focal epilepsy with consistent electroencephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 20 publications
(38 reference statements)
1
36
1
Order By: Relevance
“…Our patients displayed only mild joint laxity (which is likely related to hypotonia rather than to a connective tissue abnormality). Both had 6q27 deletions smaller than the one detected in the patient of Mosca et al [2010] (5.65 Mb); however deletion size also in this case is apparently unrelated to the presence of EDS-like features since the two patients published by Bertini et al [2006] and three out of five patients of Striano et al [2006] had deletions larger than 6 Mb but apparently lacked features of EDS.…”
contrasting
confidence: 48%
“…Our patients displayed only mild joint laxity (which is likely related to hypotonia rather than to a connective tissue abnormality). Both had 6q27 deletions smaller than the one detected in the patient of Mosca et al [2010] (5.65 Mb); however deletion size also in this case is apparently unrelated to the presence of EDS-like features since the two patients published by Bertini et al [2006] and three out of five patients of Striano et al [2006] had deletions larger than 6 Mb but apparently lacked features of EDS.…”
contrasting
confidence: 48%
“…[1][2][3][4][5][6][7][8][9]15,16 Though the clinical phenotypes associated with this deletion are quite variable, reports in unrelated subjects from independent investigators have shown that ACC, PNH, polymicrogyria, hydrocephalus, and cerebellar malformations are the consistently observed features. A recent analysis of a comprehensive map of loci for ACC from 374 patients revealed that chromosome 6q27 was one of the few loci wherein six or more subjects with ACC have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Structural brain malformations are consistently observed in these patients and include agenesis of the corpus callosum (ACC), periventricular nodular heterotopia (PNH), polymicrogyria, hydrocephalus, and cerebellar malformations. [1][2][3][4][5][6][7][8][9][10] Whereas previous studies have attempted to delineate the critical region responsible for brain malformations in patients with terminal 6q27 deletions, the sensitivity of the methodologies used has prevented the fine-mapping of the critical region. 1,6 A detailed genomic analysis of the subtelomeric chromosome 6q region would help identify the putative genes involved in the causation of brain malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Both deletions were the two largest deletions in our sample, exceeding 10 Mb. Epilepsy in 6q terminal deletion syndrome is a welldescribed feature, 16,17 whereas intellectual disability is usually the most prominent feature in 3p deletion syndrome. 18,19 As parents were not available for a significant proportion of patients, the frequency of de novo variants might be an underestimation.…”
Section: Discussionmentioning
confidence: 99%